If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 13y = 29 Solving 3x + 13y = 29 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13y' to each side of the equation. 3x + 13y + -13y = 29 + -13y Combine like terms: 13y + -13y = 0 3x + 0 = 29 + -13y 3x = 29 + -13y Divide each side by '3'. x = 9.666666667 + -4.333333333y Simplifying x = 9.666666667 + -4.333333333y
| 7d-1=5d-11 | | 2k+7=-k+7 | | 9-5w=-6w+20 | | 7+n=-6n+49 | | 7d+1=31+4d | | -10-4x=3x+46 | | 5x(x-1)= | | 12j+21=9j | | 6n+6=62-2n | | 25/x+6=5/4 | | 5a+4=67-2a | | 5+2m=6m+21 | | 2+4n=2n+22 | | a+1=5a-31 | | -6d+1=5-5d | | x+3=-45-3x | | 3t+7=42-4t | | 2m+10=3m+2 | | 10+3k=-4k+73 | | 4x(0.5+2x)= | | -6+t=3t-4 | | -3+6d=7d+9 | | -3x-2=42+x | | F(x)=4x^3-6x^2+9x+10 | | (50-x)=(.20)(50) | | 1+6d=-7d+1 | | 2+7t=-5t+14 | | 3n-9=-17+5n | | a+4=-68+7a | | 7w-1=4+2w | | -2t+2=0-4t | | 96/-16 |